G3BP2 promotes tumor progression and gemcitabine resistance in PDAC via regulating PDIA3-DKC1-hENT in a stress granules-dependent manner - Xing Fa-liang; Li Bo-rui; Fang Ying-jin; Liang Chen; Liu Jiang; Wang Wei; Xu Jin; Yu Xian-jun; Qin Yi; Zhang Bo (Acta Pharmacologica Sinica, 2025)
Pancreatic ductal adenocarcinoma (PDAC) is distinguished by its aggressive malignancy, limited treatment avenues and a tendency towards chemotherapy resistance, underscoring the critical need for advanced research to uncover new therapeutic approaches. Stress granules (SGs) that is implicated in cellular self-protection mechanism, along with its associated family molecules have shown pro-cancer effects and are closely related to tumor chemotherapy resistance. In this study we investigated the relationship between Ras GTPase-activating protein-binding proteins 2 (G3BP2), a core component of SGs, and the malignancy of PDAC as well as its resistance to the chemotherapy drug gemcitabine. Analyzing TCGA dataset revealed that the expression of G3BP1 and G3BP2 was significantly upregulated in PDAC compared with adjacent normal pancreatic tissues, and the high expression of G3BP2 rather than G3BP1 was significantly associated with poorer overall survival (OS) in PDAC patients. We demonstrated that knockdown of G3BP2 inhibited the proliferation and invasion of PANC‐1 and CFPAC-1 cells in vitro and in vivo. By analyzing the differentially expressed genes in G3BP2 knockdown and overexpressed PANC‐1 cells, we identified DKC1 that was associated with RNA stability and regulation as the target of G3BP2. We demonstrated that G3BP2 bound to PDIA3 mRNA and recruited them into SGs, increasing the stability of PDIA3 mRNA and attenuating its translation efficiency, thereby promoting DKC1 expression. Furthermore, DKC1 could bind to hENT mRNA and inhibited its expression, which enhanced gemcitabine resistance of PDAC. Therefore, we propose a novel mechanism wherein G3BP2 facilitates PDAC’s resistance to chemotherapy by modulating PDIA3-DKC1-hENT in a SGs-dependent way, suggesting G3BP2 SGs a protentional therapeutic target for the treatment in PDAC.